Determination of optimal deployment strategy for REBOA in patients with non-compressible hemorrhage below the diaphragm. Issue 1 (23rd February 2021) - Johnson, Nicholas L; Wade, Charles E; Fox, Erin E; Meyer, David E; Fox, Charles J; Moore, Ernest E; Morrison, Jonathan; Scalea, Thomas; Bulger, Eileen M; Inaba, Kenji; Morse, Bryan C; Moore, Laura J
Abstract : Background: Non-compressible truncal hemorrhage (NCTH) is the leading cause of preventable death after trauma. Resuscitative endovascular balloon occlusion of the aorta (REBOA) achieves temporary hemorrhage control, supporting cardiac and cerebral perfusion prior to definitive hemostasis. Aortic zone selection algorithms vary among institutions. We evaluated the efficacy of an algorithm for REBOA use. Methods: A multicenter prospective, observational study conducted at six level 1 trauma centers over 12 months. Inclusion criteria were age >15 years with evidence of infradiaphragmatic NCTH needing emergent hemorrhage control within 60 min of ED arrival. An algorithm characterized by the results of focused assessment with sonography in trauma and pelvic X-ray was assessed post hoc for efficacy in a cohort of patients receiving REBOA. Results: Of the 8166 patients screened, 78 patients had a REBOA placed. 21 patients were excluded, leaving 57 patients for analysis. The algorithm ensures REBOA deployment proximal to hemorrhage source to control bleeding in 98.2% of cases and accurately predicts the optimal REBOA zone in 78.9% of cases. If the algorithm was violated, bleeding was optimally controlled in only 43.8% (p=0.01). Three (75.0%) of the patients that received an inappropriate zone 1 REBOA died, two from multiple organ failure (MOF). All three patients that died with an inappropriate zone 3 REBOA died from exsanguination. Discussion: This algorithm ensures proximal hemorrhage control and accurately predicts the primary source of hemorrhage. We propose a new algorithm that will be more inclusive. A zone 3 REBOA should not be performed when a zone 1 is indicated by the algorithm as 100% of these patients exsanguinated. MOF, perhaps from visceral ischemia in patients with an inappropriate zone 1 REBOA, may have been prevented with zone 3 placement or limited zone 1 occlusion time. Level of evidence: Level III.